Mapping the use of cardiovascular genetic services in pediatric clinical care: challenges and opportunities for improvement - Hundal, Kerstin; Scherr, Courtney L.; Fakhari, Hoda; Ramesh, Sanjana; Dellefave-Castillo, Lisa; Duquette, Deb; Cherny, Sara; McNally, Elizabeth M.; Webster, Gregory; Rasmussen-Torvik, Laura J. (Frontiers in Genetics, 2025)
PurposeClinical genetic testing is increasingly integrated in managing and diagnosing cardiac conditions and disease. It is important to identify ongoing challenges. This study aimed to better understand how genetic testing is integrated into pediatric cardiac care and identify barriers and opportunities for improvement.MethodsWe conducted qualitative interviews with pediatric cardiology clinicians (N = 12). Following a journey mapping approach to data analysis, we described genetic testing workflow phases, participants’ thoughts and behaviors within each phase, and barriers and opportunities for improvement.ResultsParticipants described several challenges across the genetic testing workflow, from identifying patients for testing to disclosing results to the patients. Testing logistics, decision-making, and collaboration emerged as the most prominent challenges. Variation remains in the utilization of genetic testing, partially driven by case complexity and type of testing and attributable to other factors, like the level of interaction with genetics experts and inconsistent processes within the electronic medical record.ConclusionClinical genetic pediatric cardiology requires more systematic integration of genetic testing and transparent processes. Major opportunities include the interplay between clinicians, genetic experts, and the EMR. Incorporating process mapping results into clinical logistics may eradicate some barriers experienced by pediatric cardiologists and increase clinical efficiency.